IMF Staff papers : Volume 21 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1974)
This paper constructs three simple model of the financial effects on countries in different situations of the various arrangements regarding reserve supply that were discussed during the recent negotiations on reform of the international monetary system. Much of the analysis is devoted to an identification of the conflicting factors that determine the financial impact on a country of the possible arrangements considered. It is demonstrated that nonreserve centers have a financial interest in the existence of convertibility and in the absence of holding limits for primary assets, while the converse is true for a reserve center. Another clear-cut conclusion is that net users of special drawing rights (SDR) have a financial interest in increasing the role of the SDR by means of restrictions on reserve composition rather than by means of an increased SDR yield, while the reverse is true of countries with SDR holdings in excess of allocations.